The role of Chlamydia Trachomatis in renal tissue in the pathogenesis IGA-nephropathy related to age - I. A. Rakityanskaya; T. S. Ryabova (Журнал инфектологии)
IgA-nephropathy is the most common form of primary glomerulonephritis in the world and therefore the mechanisms of this isease are actively explored. In our study, an analysis of renal biopsy issue from 117 patients IgA-nephropathy in the presence of Chlamydia trachomatis antigen related to age (before and after 60 years). It was shown that the presence of C. trachomatis in the glomerular zone influence on the severity of segmental sclerosis (p <0.05), and its presence in the interstitium affect on the size of the glomeruli (p <0.02) and severity of degeneration of epithelial tubules (p <0.02) regardless of patient age. It was shown the effect of C. trachomatis on the expression of local immune response of kidney tissue. In patients under 60 years: C. trachomatis in the glomeruli affects the number of cells of the phenotype CD25 (p = 0,04) and CD19 / κ (p = 0,034) in the glomerular infiltration and the presence of antigen in the interstitium affect the expression of CD95 (APO-1/Fas) (p = 0,038) by mononuclear cells infiltration and formation of deposits S5b-C9 (p = 0,042) in the interstitial space. In patients older than 60 years of presence C. trachomatis in the glomerular zone impacts on the expression of TNF-α (p = 0,039) in the glomeruli, the presence of antigen in interstitium affect the number of cells CD71 (p = 0,025) in the interstitial infiltrate. Based on these results, we concluded that the presence of Chlamydia trachomatis antigen has an impact on the development and course of the disease and is the etiologic agent in patients with IgA-nephropathy, regardless of age.